2013
DOI: 10.1186/1475-2867-13-4
|View full text |Cite
|
Sign up to set email alerts
|

TWIST1, A novel androgen-regulated gene, is a target for NKX3-1 in prostate cancer cells

Abstract: BackgroundTWIST1 plays a key role in EMT-mediated tumor invasion and metastasis. Since bone metastasis is a hallmark of advanced prostate cancer and is detected in at least 85% of patients who die of this disease, it is of great importance to understand the regulation of the cellular signaling pathways involved in the metastatic process.MethodsProstatic cell lines were analyzed using real time RT-PCR, chromatin immunoprecipitations (ChIP) and transfection of siRNA’s and reporter constructs.ResultsWe report in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 19 publications
1
22
1
1
Order By: Relevance
“…As shown in Fig. 1A, endogenous Twist1 mRNA expression and protein were significantly induced by R1881 treatment in LNCaP cells, consistent with an earlier study reporting androgen regulation of Twist1 (Eide et al, 2013); LNCaP cells express AR and exhibit androgen-dependent cell growth (Horoszewicz et al, 1983). As expected (Jenster, 1999), androgen caused upregulation of AR in LNCaP cells (Fig.…”
Section: Androgen Treatment Induces Twist1 Expression In Androgendepesupporting
confidence: 89%
“…As shown in Fig. 1A, endogenous Twist1 mRNA expression and protein were significantly induced by R1881 treatment in LNCaP cells, consistent with an earlier study reporting androgen regulation of Twist1 (Eide et al, 2013); LNCaP cells express AR and exhibit androgen-dependent cell growth (Horoszewicz et al, 1983). As expected (Jenster, 1999), androgen caused upregulation of AR in LNCaP cells (Fig.…”
Section: Androgen Treatment Induces Twist1 Expression In Androgendepesupporting
confidence: 89%
“…Note that not all pathways discussed in the manuscript are shown in this figure between these two proteins may exist. AR also upregulates NKX3-1, which represses TWIST1 via binding to the TWIST1 promoter [66]. Contrary to the above findings, which suggest that AR inhibits EMT, ectopic expression of AR in BPH-1 cells induces EMT, whereas knockdown of AR downregulates EMT markers [67], suggesting that AR may play a different role in culture conditions than within the tumor microenvironment.…”
Section: Signaling In Epcontrasting
confidence: 53%
“…Twist 1 was found to bind to E-boxes, 5'-CANNTG-3', in the proximal promoter (-442 to +51 bp) and upstream regions (-539 to -974 bp and -1187 to -1589 bp) (Eide et al 2013). However, it has also been reported that androgens upregulate Twist 1 expression, observed in prostate cancer microarrays (Ngan et al 2009), and in LNCaP cells after 72 hours of treatment with the powerful androgen agonist R1881 (Eide et al 2013). These apparently contradictory findings appear to be due to the differing timescales used, with an initial downregulation of Twist 1 expression by increased NKX3-1 eventually being overcome by androgen upregulation.…”
Section: Androgens and The Process Of Epithelial Mesenchymal Transitionmentioning
confidence: 99%